Analisis Disiplin Kerja Pegawai Negeri Sipil Pada Kantor Kecamatan Nusaniwe Kota Ambon - Sakir, Ahmad Rosandi (LPPM STIA Lancang Kuning Dumai, 2024)
The ability of employees at the Subdistrict Office of Nusaniwe, Ambon City, to comply with duties and avoid prohibitions is by the provisions of Government Regulation Number 53 of 2010 concerning the Discipline of Civil Servants. These duties include aspects such as attendance and adherence to working hours, achieving work targets as specified, and providing the best possible service to the community by applicable Service Standards. The applicable prohibitions cover aspects such as receiving gifts or rewards from various parties that may be related to work or positions, as well as restraining or obstructing those being served, potentially causing losses to the parties involved. Furthermore, disciplinary action involves determining the level and type of disciplinary action commensurate with the violations committed by employees.